Family caregiver use and value of support services in the VA Program of Comprehensive Assistance for Family Caregivers - Nina Sperber; Courtney Van Houtven; Sara Andrews; Katherine Miller; Karen Steinhauser; G. Darryl Wieland; Valerie Smith; Jennifer Lindquist; Megan Shepherd-Banigan; Margaret Campbell-Kotler; Jennifer Henius; Margaret Kabat (Journal of Long-Term Care, 2018)
Context:The US Congress in 2010 established the Program of Comprehensive Assistance for Family Caregivers (PCAFC) in the Department of Veterans Affairs’ (VA) healthcare system, expanding services for family caregivers of eligible veterans with injuries sustained or aggravated in the line of duty on or after 11 September 2001. The program includes a Caregiver Support Coordinator, stipends for caregivers, education/training, and additional services. Objective: The primary goal of this study was to examine the types of services that family caregivers of veterans use and value, how services are used and any limitations family caregivers’ experienced. Given that few interventions assess caregiver satisfaction with services, there is a gap in the existing literature addressing these outcomes.